Ideologies in Mandelas No Easy Walk to Freedom - AbdulhameedFaris, Ali; Paramasivam, Shamala (Australian International Academic Centre, 2016)
Ideology has great influence on the traits and behaviors of leaders. It is the vehicle by which we could understand our leaders and our leaders could understand us. The present paper is an endeavor to reveal the ideological dimension that is embedded in the discourse of Nelson Mandela, with special reference to his address No Easy Walk to Freedom which was delivered in 1953. It is conducted on the approach of Critical Discourse Analysis. Van Dijk's (2004) Political Ideological Strategies and Wodak's (2005) Discursive Strategies of Positive Self- and Negative Other-Presentation were accommodated to achieve the objective of the study. The findings demonstrated that Van Dijk's strategies of actor description, positive self-presentation and negative other-presentation and Wodak's two chosen strategies of argumentation and perspectivation were supportive in exploring the ideologies penetrated in Mandela's discourse. They five strategies proved to be helpful devices in exploring the fundamentally embedded ideologies in Mandela's discourse which are "white superiority" and "black inferiority". White superiority was the ideological foundation of the white minority to establish the apartheid system in South Africa for decades, whereas black inferiority was the ideological foundation of the black majority to sustain different forms of resistance against the white governments. Therefore, it could be perceived that the social acts of both the blacks and the whites were formed and structured in terms of these two ideological foundations.